Children as members of a community: Citizenship, participation and educational development – an introduction to the special issue. (March 2015) - Lúcio, Joana; I'Anson, John
For the purpose of this publication, the authors shall discuss the subject of young people as citizens and, particularly, as members of a community. Their focus shall be on how young people perceive themselves as members of one (or several) community(ies), and on how communitarian interactions (at an interpersonal and/or an organizational level) are viewed, by them, as fundamental for their own development and for that of the community(ies) to which they belong. The contributions featured in this special issue invoke a broad understanding of participation and citizenship in terms of children's everyday experiences, informed by their roles as members of one (or several) family(ies), as students, as inhabitants of a certain space, etc. These different roles emerge both as products and as constructs of the different 'stages' upon which the child acts: they are contexts of individual but also collective – and eventually communitarian – action and appropriation. The concept of community as dialectics is especially relevant here, since what is sought is not consensus, but rather participation, which, in its plurality of forms, warrants the emergence of initiatives that really correspond to the individuals' demands. The 'common', rather than smothering diversity, emerges with the purpose of configuring fuller and more complex ways of experiencing citizenship and citizens' rights.